Climate change and allergic diseases: An overview - Singh, A. B.; Kumar, Pawan (Frontiers in Allergy, 2022)
Climate change has been regarded as threat to human species on the earth. Greenhouse gasses are leading to increased temperature of Earth besides impacting the humanity. These atmospheric conditions have shown to alter the release pattern of pollens and can change the timing and magnitude of pollen release by flowering plants. As pollen are responsible for respiratory allergies in humans, so climate change can adversely affect human health in the susceptible individuals. In this review, we highlight association between climate change, increased prevalence and severity of asthma and related allergic diseases. Increased air pollution can alter local and regional pollen production. This altered pattern depends on bioclimatic parameters. As simulated with a pollen release model and future bioclimatic data, warmer temperatures lead to increased pollen count in some specific locations and for longer periods. Thus, anticipation of future allergic disease burden can help the public health agencies in planning to develop strategies in mitigating unprecedented health challenge expected in coming years.